THE DYNAMICS OF IMAGERY IN LINGUISTIC CREATIVITY AND INNOVATION - Mamurova, Shakhlo (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
Linguistic creativity reflects the innovative nature of communities and cultures. This paper presents initial findings from an empirical project that examines the characteristics and pace at which winged words and neologisms spread on a microblogging platform. The study utilizes social network analysis tools to process large-scale data. Understanding the spread of linguistic innovation requires an interdisciplinary approach, combining insights from human, social, and computational sciences. By adopting a complex systems perspective, this research aims to provide a deeper understanding of how interactions and communication between internet users influence the cultural evolution of language over time and across different spaces. It also explores how these interactions shape linguistic trends, offering quantitative insights into the expansion of linguistic expressions and predicting future developments.